Cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material and preparation method thereof, negative electrode plate and battery
The cobalt tungstate composite reduced graphene oxide negative electrode material prepared by the ultrasonic-hydrothermal method solves the capacity and stability problems of traditional materials, realizes the application of high-performance lithium-ion batteries, and has a simple and low-cost preparation process.
Patent Information
- Application Number
- CN202510953641.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-10-17
AI Technical Summary
Traditional graphite negative electrode materials have low theoretical capacity, transition metal oxides have poor conductivity and poor cycle stability, nanoparticles are prone to agglomeration, and the existing graphene composite material preparation process is complex and costly.
Cobalt tungstate composite reduced graphene oxide (CoWO4@RGO) anode material was prepared by ultrasonic-hydrothermal synthesis method. The morphology and particle size of the nanomaterial were controlled by coprecipitation-hydrothermal method to form a petal-shaped nanosheet structure, thereby improving the conductivity and structural stability.
The prepared CoWO4@RGO negative electrode material has uniform particle size, high specific capacity, excellent rate performance and long cycle stability. The simple preparation method reduces the cost and is suitable for large-scale production.
Smart Images

Figure CN120793913A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of lithium ion battery negative electrode materials, in particular to a cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material and a preparation method, a negative electrode sheet and a battery. BACKGROUND
[0002] With the surge in demand for lithium ion batteries, the traditional graphite negative electrode is difficult to meet the demand for high energy density due to its low theoretical capacity (372 mAh / g). Although transition metal oxides (such as CoWO4) have high specific capacity (>500 mAh / g), they have poor electrical conductivity and large volume expansion during charging and discharging, resulting in poor cycle stability. In the prior art, the use of graphene composite materials can improve the electrical conductivity, but there are the following problems: the nanoparticles are prone to agglomeration, resulting in low utilization rate of active sites; the preparation process is complex (such as high-temperature reduction and multi-step coating), and the cost is high. SUMMARY
[0003] Therefore, the application provides a cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material and a preparation method, a negative electrode sheet and a battery. The cobalt tungstate composite reduced graphene oxide negative electrode nanomaterial (CoWO4@RGO) is obtained by a simple ultrasonic-hydrothermal synthesis method. The negative electrode nanomaterial prepared by the method has uniform and small particle size, and the size is about 100-200 nm, solving the problem of easy agglomeration of nanoparticles. The material can also effectively accelerate the transmission of ions and electrons, so that the material has high specific capacity, excellent rate performance and long cycle stability when used as a lithium ion battery negative electrode. In addition, the preparation method is simple and can be scaled up for production, and the operation steps are controllable.
[0004] The first aspect of the application provides a preparation method of a cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material, comprising the following steps:
[0005] Step one, dissolving a carbon source and a cobalt source in deionized water, ultrasonic dispersion, denoted as solution A, then dissolving a sodium source in deionized water, denoted as solution B, and stirring the solution A and the solution B for a period of time respectively;
[0006] Step two, slowly adding the stirred solution B to the continuously stirred solution A to obtain solution C, and then ultrasonic treatment for a period of time;
[0007] Step three, performing hydrothermal reaction on the ultrasonic-treated solution C to generate a precipitate denoted as precursor D; taking out the precursor D after natural cooling to room temperature, centrifuging, washing and drying to obtain the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material.
[0008] Preferably, in step one, the cobalt source is cobalt acetate hexahydrate; the sodium source is sodium tungstate dihydrate; and the carbon source is reduced graphene oxide.
[0009] Preferably, in step one, the ultrasonic time is 20 min; and the stirring time is 20 min.
[0010] Preferably, in step two, the dropping speed is 3.980 mm / min.
[0011] Preferably, in step three, the hydrothermal reaction temperature is 180℃, and the hydrothermal reaction time is 10 h.
[0012] Preferably, in step three, the centrifugal speed is 4000 r / min, and the centrifugal time is 2 min.
[0013] Preferably, in step three, the washing is performed by using deionized water and anhydrous ethanol alternately for 3 times; and the drying temperature is 80℃.
[0014] The second aspect of the application further provides a cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material, which is prepared by the above method.
[0015] The third aspect of the application further provides a negative electrode sheet, which contains the above cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material or the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material prepared by the above method.
[0016] The fourth aspect of the application further provides a battery, which includes the above negative electrode sheet, and further includes a battery shell, a positive electrode sheet, a separator and an electrolyte.
[0017] Compared with the prior art, the application has the following beneficial effects:
[0018] 1. The CoWO4@RGO negative electrode nanomaterial prepared by the application is prepared by loading cobalt tungstate on the surface of reduced graphene oxide and using a co-precipitation-hydrothermal method, and has a petal-shaped nanosheet structure; in addition, the co-precipitation-hydrothermal method can further reduce the grain size of the CoWO4@RGO negative electrode nanomaterial, thereby improving the ionic conductivity of cobalt tungstate, the lithium extraction and lithium intercalation capacity, improving the electrical conductivity of cobalt tungstate and the structural stability of the material, and increasing the specific surface area, so that the material exhibits excellent cycle stability and rate performance as a lithium battery negative electrode material.
[0019] 2、The CoWO4@RGO negative nanomaterial prepared by the ultrasonic-hydrothermal method of the application has uniform and small particle size, and the size is about 100-200 nm, which can effectively accelerate the transmission of ions and electrons, so that the synthesized material has more excellent capacity and rate performance for the lithium ion battery negative electrode.
[0020] 3、The preparation method adopted by the application is simple, fast and the raw materials adopted are low in price; first, low-cost and easily available starting materials are selected, the synthesis method does not need expensive raw materials, devices or complex synthesis conditions, greatly reducing the complexity and cost in the preparation process, and having practical application value.
[0021] 4、The negative material prepared by the application has excellent electrochemical performance, and in the electrochemical test, the material shows high discharge specific capacity and good cycle life, which shows that the material has potential in the application of lithium ion batteries and can meet the needs of performance and cycle life.
[0022] 5、The CoWO4@RGO prepared by the application can be used as a high-performance lithium ion battery negative electrode material; the specific capacity of the CoWO4@2% RGO electrode material is 450.1 mAh / g after 100 times of charge and discharge at a high current density of 500 mA / g, which shows that the CoWO4@2% RGO negative electrode material has application potential in the application of high-performance lithium ion batteries. BRIEF DESCRIPTION OF DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the application or the prior art, the following will briefly introduce the drawings needed to be used in the description of the application or the prior art. Obviously, the drawings described below are some embodiments of the application, and those skilled in the art can also obtain other drawings according to these drawings without creative labor.
[0024] Figure 1 XRD spectra of the negative nanomaterials of Examples 1-3 and Comparative Example 1 of the application;
[0025] Figure 2 Rate graph of the negative nanomaterials of Examples 1-3 and Comparative Example 1 of the application;
[0026] Figure 3 Long cycle graph of the negative nanomaterials of Examples 1-3 and Comparative Example 1 of the application;
[0027] Figure 4 SEM graph of the CoWO4@RGO negative nanomaterial of Example 3 of the application. DETAILED DESCRIPTION
[0028] In order to make the purposes, technical solutions and advantages of the present application clearer, the technical solutions in the present application will be described clearly and completely below in conjunction with the drawings in the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present application.
[0029] The experimental methods used in the embodiments of the present application are all conventional methods unless otherwise specified.
[0030] In the following examples and comparative examples, all raw materials can be obtained by commercial purchase or conventional methods unless otherwise specified, and the specific methods are as follows: cobalt acetate hexahydrate (Shanghai Maikelin Biochemical Technology Co., Ltd., 99%), sodium tungstate dihydrate (Shanghai Maikelin Biochemical Technology Co., Ltd., 99%), RGO (Jiaoshaoye Guangdong New Material Co., Ltd., 95%).
[0031] Example 1
[0032] First, 0.887 g of cobalt acetate, 1.326 g of sodium tungstate and RGO according to 1% mass percentage were weighed, two portions of 30 ml of deionized water were measured, RGO and cobalt acetate were dissolved in deionized water, and ultrasonic dispersion was performed for 20 min, which was recorded as solution A; sodium tungstate was dissolved in deionized water, which was recorded as solution B, and was placed in a magnetic stirrer for stirring; after solution A and solution B were stirred for 20 min, a 10 ml syringe containing solution B was fixed on a sample pump, and solution B was slowly added to the continuously stirred solution A at a sample injection speed of 3.980 mm / min to obtain solution C, and then ultrasonic treatment was performed for 20 min; after the ultrasonic treatment was completed, solution C was slowly poured into a polytetrafluoroethylene liner, placed in a steel sleeve and tightened; then the steel sleeve was placed in a 180℃ air drying oven for 10 h for hydrothermal reaction, and the precipitate generated in the reaction was recorded as precursor D; after the precursor D was naturally cooled to room temperature, it was taken out, centrifuged at 4000 r / min for 2 min, washed with deionized water and anhydrous ethanol alternately for 3 times, and then placed in a 80℃ air drying oven for drying, and finally CoWO4@1% RGO negative electrode nanomaterial was obtained.
[0033] Example 2
[0034] Firstly, 0.887 g of cobalt acetate, 1.326 g of sodium tungstate, and RGO according to 2% mass percentage are weighed, two portions of 30 ml of deionized water are measured, RGO and cobalt acetate are dissolved in deionized water, and ultrasonic dispersion is performed for 20 min, which is recorded as solution A; sodium tungstate is dissolved in deionized water, which is recorded as solution B; and the two solutions are respectively placed in a magnetic stirrer for stirring; after solution A and solution B are stirred for 20 min, a 10 ml syringe containing solution B is fixed on a sample pump, and solution B is slowly added to continuously stirred solution A at a sample injection speed of 3.980 mm / min to obtain solution C, which is then ultrasonically treated for 20 min; after ultrasonic treatment, solution C is slowly poured into a polytetrafluoroethylene liner, placed in a steel sleeve, and tightened; then the steel sleeve is placed in a 180℃ air drying oven for 10 h for hydrothermal reaction, and the precipitate generated in the reaction is recorded as precursor D; after natural cooling of precursor D to room temperature, it is taken out, centrifuged at 4000 r / min for 2 min, washed with deionized water and anhydrous ethanol alternately for 3 times, and then placed in a 80℃ air drying oven for drying, to finally obtain CoWO4@2% RGO negative electrode nanomaterial.
[0035] Example 3
[0036] Firstly, 0.887 g of cobalt acetate, 1.326 g of sodium tungstate, and RGO according to 2% mass percentage are weighed, two portions of 30 ml of deionized water are measured, RGO and cobalt acetate are dissolved in deionized water, and ultrasonic dispersion is performed for 20 min, which is recorded as solution A; sodium tungstate is dissolved in deionized water, which is recorded as solution B; and the two solutions are respectively placed in a magnetic stirrer for stirring; after solution A and solution B are stirred for 20 min, a 10 ml syringe containing solution B is fixed on a sample pump, and solution B is slowly added to continuously stirred solution A at a sample injection speed of 3.980 mm / min to obtain solution C, which is then ultrasonically treated for 20 min; after ultrasonic treatment, solution C is slowly poured into a polytetrafluoroethylene liner, placed in a steel sleeve, and tightened; then the steel sleeve is placed in a 180℃ air drying oven for 10 h for hydrothermal reaction, and the precipitate generated in the reaction is recorded as precursor D; after natural cooling of precursor D to room temperature, it is taken out, centrifuged at 4000 r / min for 2 min, washed with deionized water and anhydrous ethanol alternately for 3 times, and then placed in a 80℃ air drying oven for drying, to finally obtain CoWO4@2% RGO negative electrode nanomaterial.
[0037] Comparative Example 1
[0038] Firstly, 0.887 g of cobalt acetate, 1.326 g of sodium tungstate and RGO according to 0% mass percentage were weighed, two 30 ml deionized water were measured, cobalt acetate was dissolved in deionized water, ultrasonic dispersion was carried out for 20 min, and the solution was recorded as solution A; sodium tungstate was dissolved in deionized water and recorded as solution B, and was placed in a magnetic stirrer for stirring; after solution A and solution B were stirred for 20 min, a 10 ml syringe containing solution B was fixed on a sample pump, and solution B was slowly added to the continuously stirred solution A at a sample injection speed of 3.980 mm / min to obtain solution C, and then ultrasonic treatment was carried out for 20 min; after the ultrasonic treatment was completed, solution C was slowly poured into a polytetrafluoroethylene liner, placed in a steel sleeve and tightened; then the steel sleeve was placed in a 180℃ air drying oven for 10 h for hydrothermal reaction, and the generated precipitate was recorded as precursor D; after the precursor D was naturally cooled to room temperature, it was taken out, centrifuged at 4000 r / min for 2 min, washed with deionized water and anhydrous ethanol alternately for 3 times, and then placed in a 80℃ air drying oven for drying, and finally CoWO4 negative electrode nanomaterial was obtained.
[0039] XRD test
[0040] The materials prepared in Examples 1-3 and Comparative Example 1 were subjected to XRD test, and the test results are shown in Figure 1 From Figure 1 it can be seen that the diffraction peaks at diffraction angles (2θ) of 15.48°, 18.91°, 23.84°, 24.57°, 30.47°, 31.26°, 36.31°, 36.77°, 38.34°, 41.15°, 41.32°, 48.76°, 50.28° and 51.72° respectively correspond to the characteristic diffraction peaks of the standard card of PDF#73-0554, and no other impurity phase is found, indicating that the CoWO4@RGO negative electrode nanomaterial has high crystallinity. It is shown that the synthesized product achieves the expected goal.
[0041] SEM test
[0042] The material prepared in Example 3 was subjected to SEM test, and the test results are shown in Figure 4 From Figure 4 it can be seen that the CoWO4@RGO negative electrode nanomaterial powder is composed of many petal-shaped nanosheets. The nanosheet size is uniform, the morphology is solid regular nanosheet, and the particle size of the sheet body is micro-nanometer level, which indicates that the material has a good specific surface area and an excellent lithium intercalation and deintercalation capacity.
[0043] Battery performance test
[0044] The products of Examples 1-3 and Comparative Example 1 were used as electrode materials of lithium ion batteries
[0045] (1) The materials of Examples 1-3 and Comparative Example 1 were mixed with the conductive agent Super P and PVDF in a mass ratio of 8:1:1, ground and mixed uniformly in a mortar, and coated on a copper foil with an appropriate amount of NMP, dried in a vacuum drying oven at 80°C for 12 h, and then obtained as a battery negative electrode sheet after rolling and cutting;
[0046] (2) A 2016-type coin cell was prepared in an argon-filled glove box using a lithium metal sheet as the counter electrode, a celgard2250 separator as the separator, and a 1M LiPF6 / EC:DEC (volume ratio 1:1) electrolyte. The prepared 2016-type coin cell was tested for battery performance on a blue cell test system. The electrochemical energy storage performance of the prepared lithium ion battery was tested.
[0047] (3) The charge and discharge range was 0.01-3V, and the charge and discharge rate was 500mA / g, 1000mA / g, 2000mA / g, 3000mA / g, and 5000mA / g. The electrochemical energy storage performance of the prepared lithium ion battery was tested, as shown in Figure 2 and Figure 3 .
[0048] As can be seen from Figure 2 , the CoWO4@2%RGO negative nanomaterial prepared in Example 2 has a charge specific capacity of about 657.9mAh / g, 383.5mAh / g, 247.5mAh / g, 207.9mAh / g, and 99.5mAh / g at a current density of 500mA / g, 1000mA / g, 2000mA / g, 3000mA / g, and 5000mA / g, and a capacity retention rate of 95.34%, 97.66%, 98.74%, 99.66%, and 99.89%, respectively. The performance is better than that of other examples. This indicates that the lithium ion battery prepared from the CoWO4@2%RGO negative nanomaterial has good rate performance and a high capacity retention rate.
[0049] As can be seen from Figure 3 , the CoWO4@2%RGO negative nanomaterial prepared in Example 2 has a specific capacity of about 450.1mAh / g after 90 cycles at a current density of 500mA / g, and a capacity retention rate of about 98.27%. This indicates that the lithium ion battery prepared from the CoWO4@2%RGO negative nanomaterial has good cycle performance and a low decay rate.
[0050] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application, but not to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material, characterized in that: The following steps are involved: Step 1: dissolving a carbon source and a cobalt source in deionized water, and ultrasonically dispersing the solution, which is referred to as solution A. Then, dissolving a sodium source in deionized water, which is referred to as solution B, and stirring the solution A and solution B for a period of time respectively; Step 2: slowly add the stirred solution B dropwise to the continuously stirred solution A to obtain solution C, which is then ultrasonicated for a period of time; Step 3: The ultrasonically treated solution C is subjected to a hydrothermal reaction, and the resulting precipitate is recorded as a precursor D; the precursor D is naturally cooled to room temperature and then taken out, centrifuged, washed, and dried to obtain a cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material.
2. The method for preparing the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 1, the cobalt source is cobalt acetate hexahydrate; the sodium source is sodium tungstate dihydrate; and the carbon source is reduced graphene oxide.
3. The method for preparing the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 1, the ultrasonic time is 20 min; the stirring time is 20 min.
4. The method for preparing the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the dropping acceleration is 3.980 mm / min.
5. The method for preparing the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 3, the hydrothermal reaction temperature is 180° C. and the hydrothermal reaction time is 10 h.
6. The method for preparing the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 3, the centrifugal speed is 4000 r / min and the centrifugal time is 2 min.
7. The method for preparing the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 3, the washing is performed by alternating deionized water and anhydrous ethanol for 3 times; and the drying temperature is 80°C.
8. A cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material, characterized in that: A cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material prepared by the method according to any one of claims 1 to 7.
9. A negative electrode sheet, characterized in that: The negative electrode sheet contains the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material according to claim 8 or the cobalt tungstate composite reduced graphene oxide lithium ion battery negative electrode material prepared by the method of any one of claims 1-7.
10. A battery, characterized in that: The invention comprises the negative electrode sheet according to claim 9, and further comprises a battery casing, a positive electrode sheet, a separator and an electrolyte.